2013
DOI: 10.1039/c3cp51018b
|View full text |Cite
|
Sign up to set email alerts
|

Highly soluble energy relay dyes for dye-sensitized solar cells

Abstract: High solubility is a requirement for energy relay dyes (ERDs) to absorb a large portion of incident light and significantly improve the efficiency of dye-sensitized solar cells (DSSCs). Two benzonitrile-soluble ERDs, BL302 and BL315, were synthesized, characterized, and resulted in a 65% increase in the efficiency of TT1-sensitized DSSCs. The high solubility (180 mM) of these ERDs allows for absorption of over 95% of incident light at their peak wavelength. The overall power conversion efficiency of DSSCs with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 37 publications
(48 reference statements)
0
29
0
Order By: Relevance
“…8,9 Hardin et al 8 reported an unattached energy donor (ED) dissolved in electrolyte solution, excited by higher energy photons and efficiently transferring its excitation energy to a dye sensitizer (DS), which increases the absorption spectral bandwidth of the cell and improves the power conversion efficiency from 2.55 to 3.21%. However, the cell performance is decreased because of several factors: [8][9]19,21 (1) dynamic quenching by electrolytes (I 3 − ), (2) self-absorption between EDs and (3) the formation of aggregates between the ED and DS. We demonstrated that iQDs encapsulated by the nanofiber can overcome the problems described above and also can efficiently transfer energy to dye sensitizers, increasing the overall power conversion efficiency and durability of the DSC.…”
Section: Distribution Of Quantum Dots In Nanofibermentioning
confidence: 99%
See 2 more Smart Citations
“…8,9 Hardin et al 8 reported an unattached energy donor (ED) dissolved in electrolyte solution, excited by higher energy photons and efficiently transferring its excitation energy to a dye sensitizer (DS), which increases the absorption spectral bandwidth of the cell and improves the power conversion efficiency from 2.55 to 3.21%. However, the cell performance is decreased because of several factors: [8][9]19,21 (1) dynamic quenching by electrolytes (I 3 − ), (2) self-absorption between EDs and (3) the formation of aggregates between the ED and DS. We demonstrated that iQDs encapsulated by the nanofiber can overcome the problems described above and also can efficiently transfer energy to dye sensitizers, increasing the overall power conversion efficiency and durability of the DSC.…”
Section: Distribution Of Quantum Dots In Nanofibermentioning
confidence: 99%
“…If EDs are dissolved in electrolyte solution, 8 however, energy transfer from ED to DS should be decreased by the above two interactions. 21 In equation (1),…”
Section: Distribution Of Quantum Dots In Nanofibermentioning
confidence: 99%
See 1 more Smart Citation
“…Dye A was chosen after a literature survey on fluorophore structures thanks to its interesting optical properties and easy synthesis in view of a possible application in low‐cost down‐shifting polymers or as a co‐absorber . The simplest and cheapest way to obtain this dye is from the reaction between dansyl chloride and 6‐aminohexanoic acid, through a nucleophilic substitution between the chlorine and amine (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Complementary dyes can be used in DSSCs to improve efficiency, the first one bound to titania, and the second one dispersed in the electrolyte to act as a complementary pigment (energy relay dyes), which mimics the photosynthetic process. The dispersion of DSSC dyes in LDHs allows their facile use in the melt blending extrusion of polymers.…”
Section: Introductionmentioning
confidence: 99%